Acute Intermittent Prophyria Presenting as Acute Abdomen - Khattak, Muhammad Ishaq; Rahman, Faiz ur (Journal of Postgraduate Medical Institute, 2011)
The porphyrias are a group fo diseases characterized by the overproduction of porphyrin compounds and their precursors. In animals, porphyrin synthesis is required for the production of heme. Just as the iron - containing porphyrin heme cataliyzes oxidative phosphoryelation in animals, the magnesium containing porphyrin chlorophyll catalyzes photosynthesis. As more poetically described by the nobel prize winner Hans Fischer, porphyrins are the substances that make blood red and grass green.